Pergumulan Partai Politik Islam Pada Masa Demokrasi Terpimpin: Masyumi Tumbang, NU Melenggang, PSII Bimbang - Muhammad Rijal Fadli (JUSPI (Jurnal Sejarah Peradaban Islam), 2020)
This article aims to review the struggle of Islamic political parties during the guided democracy era. The research method used is historical with a literature study approach. The results of the study explain that in Indonesia's history, records regarding the democratic order that brought President Soekarno to the top of his highest government, namely from 1957 to 1965. The role of Indonesian democracy did not only decline but almost changed to become a dictator. In the end, Soekarno's guided democracy idea was responsive from Indonesian political activists, including from Islamic political parties. Soekarno's idea, the Islamic political party pursued a two-sided path, one side firmly rejected and one side supported it. This difference in interests has brought the two camps into a political struggle during the guided democracy era. The contra group represented by Masyumi got the impact of their ideology with the dissolution of this party. Meanwhile, support groups such as NU even gained political triumph during the guided democracy era. Artikel ini bertujuan mengulas kembali tentang pergumulan partai politik Islam masa demokrasi terpimpin. Metode penelitian yang digunakan adalah historis dengan pendekatan studi pustaka. Hasil penelitian menjelaskan dalam sejarah Indonesia mencatat mengenai tatanan demokrasi yang membawa presiden Soekarno ke puncak pemerintahan tertingginya, yakni pada masa 1957 hingga 1965. Peranan demokrasi Indonesia tidak hanya menurun, melainkan hampir saja berganti menjadi diktator. Pada akhirnya gagasan demokrasi terpimpin Soekarno memunculkan responsif dari para penggiat politik Indonesia, termasuk dari partai politik Islam. Dalam menanggapi gagasan Soekarno, partai politik Islam menempuh jalan bersibak dua, satu sisi menolak tegas dan satu sisi mendukungnya. Perbedaan kepentingan ini telah membawa kedua kubu ke dalam pergumulan politik pada masa demokrasi terpimpin. Kelompok kontra yang diwakili oleh Masyumi mendapat imbas dari ideologi mereka dengan dibubarkannya partai ini. Sedangkan kelompok pendukung seperti NU malah mendapatkan kejayaan politik pada masa demokrasi terpimpin.